Implementation of Curriculum 2013 through Best Practice - Jumadi Jumadi (Pusat Studi Penelitian dan Evaluasi Pembelajaran, 2020)
The Curriculum 2013 will soon be implemented in all education units in the 2016/2017 school year, after going through a fairly tough process in the 2013/2014, 2014/2015 and 2015/2016 academic years so that it is only applied in a limited manner to a few educational units. Technical matters in the curriculum are indeed important for the successful implementation of education. However, there is one thing that should not be forgotten, namely how the teacher's creative process is in finding the best learning practices based on the experiences and practices that he has applied when teaching. The various ways and methods that have been applied by the teacher in teaching have made the teacher find new methods which are a Best Practice in teaching. The formulation of best practices in the context of implementing the Curriculum 2013 is carried out through various approaches, namely: 1) Building a learning culture in schools. 2) Using a scientific approach with various types of active learning activities. 3) Relying on the skills of teachers in carrying out active learning in schools. 4) Changing aspects of attitudes, interest in learning, thinking skills, and ways of mastering learning concepts according to the best practice matrix in the context of implementing the 2013 Curriculum that has been formulated in this paper. The steps to get best practice can be done by following the steps as follows: 1) Observing the situation; 2) Motivation; 3) Measurement of results and impacts; 4) Sustainable; 5) Experience that needs to be learned (lessons learned) and (action plan); 6) Potential for development; and 7) Comparative Study.